Clinical Characteristics and Cytogenetics of Childhood Acute Lymphoblastic Leukemia in a Single Center in Pakistan - Najia Tabassum MBBS, MPhil; Sadia Muhammad MBBS, FCPS (Peads); Talat Mirza MBBS, MPhil, PhD; Zainab Butt MBBS; Neelum Mansoor MBBS, FCPS (Heam) (SAGE Publishing, 2024)
Objectives. This study aimed to find the association between clinical characteristics, cytogenetics, and post-induction outcomes of childhood acute lymphoblastic leukemia. Methods. The study was conducted at the Indus Hospital in Karachi. Initial total leukocyte count (TLC), cytogenetics, CNS status, and post-induction remission status were recorded. Results. Out of 108 children diagnosed with ALL, 66 (61.1%) were male and 42 (38.9%) were female. The majority 90 (83.3%) had B-ALL. CNS1 status was observed in 76 (84.4%) B-ALL and 18 (88.9%) T-ALL. All T-ALL and 89 (98.8%) B-ALL achieved remission post-induction. In B-ALL, 50 (55.5%) had a normal diploid karyotype, and 22 (24.4%) had numerical abnormalities. No typical gene rearrangement was observed in 66 (73.3%), 11 (12.2%) had BCR::ABL1, 10 (11.1%) had ETV6::RUNX1 and 3 (3.3%) KMT2A on FISH. No significant difference was observed between cytogenetics and clinical characteristics ( P  > .05). Conclusion. The study provides valuable data on childhood acute lymphoblastic leukemia in the Pakistani population.